1960
DOI: 10.1111/j.1438-8677.1960.tb00003.x
|View full text |Cite
|
Sign up to set email alerts
|

ON THE ABSCISSION OF DEBLADED PETIOLES INCOLEUS RHENALTIANUS, ESPECIALLY IN RELATION TO THE EFFECT OF GRAVITY

Abstract: By means of experiments with Coleus rhenaltianus it could be demonstrated that the effect of proximally as well as of distally applied auxin (IAA) on the abscission of debladed petioles, is an indirect one. By growth processes that are induced by the application of auxin at the proximal side of the abscission zone, e.g. by the development of new adventitious roots and by the elongation of roots that are already present, a substance that retards the abscission is drained off from the petioles. This substance is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

1962
1962
1983
1983

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 97 publications
1
20
0
Order By: Relevance
“…Terpstra (86) and Vendrig (94) confirmed the effects of both tip-excision and IAA-substitution, using a different species of Coleus. IAA in lanolin at 0.2 per cent (86), or 5 or 50 ppm (94), replaced the abscission-speeding effect of the tip of the experimental plants (the apical bud plus unfolded leaf-pairs numbers 1 and 2) on debladed leaves numbers 3 and 4.…”
Section: Jacobssupporting
confidence: 55%
“…Terpstra (86) and Vendrig (94) confirmed the effects of both tip-excision and IAA-substitution, using a different species of Coleus. IAA in lanolin at 0.2 per cent (86), or 5 or 50 ppm (94), replaced the abscission-speeding effect of the tip of the experimental plants (the apical bud plus unfolded leaf-pairs numbers 1 and 2) on debladed leaves numbers 3 and 4.…”
Section: Jacobssupporting
confidence: 55%
“…In all cases the presence of the apical bud had a promotive influence on leaf abscission, and auxin applied in place of the apical bud had a similar, sometimes even greater, promotive effect (14,19,21,29,32).…”
Section: Addicottmentioning
confidence: 95%
“…Most of the reported results fall between these types, with either monophasic curves (8, 9, 10, 13, 17, 20, 22, 32 and Figs. 1 and 2 of this paper) or diphasic curves (10,12,14,23,32 …”
Section: Addicottmentioning
confidence: 99%
See 1 more Smart Citation
“…Vendrig (16) reported that it controls the longitudinal tralnsport in Colcius stems of a substance which retards abscission of leaves btut his methods indicated that the basipetal nmovement of neither endogenous nor exogenous IAA is affected by gravity. For cases of reduced elongation of stems kept for some time in the horizontal position, as in the work of Wareing and Nasr (17) with voo(ly branches, Vendrig favored indirect control of g-rowth by correlative effects rather than by retarded transl)ort of growth regulators.…”
Section: Lyon-action Of Gravity On B-xslpetal Transport Of Auxin95 DImentioning
confidence: 99%